Implementasi Edupreneurship Melalui Business Center di SMKN 1 Kaligondang - Muginah, Muginah; Kusumawardhana, Ap Massri M; Winarso, Didik; Suwardi, Suwardi; Kuat, Tri (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to describe and analyze the implementation of edupreneurship through the business center at SMKN 1 Kaligondang and how to foster an entrepreneurial spirit in students through this program. The research method used is a qualitative method, which aims to understand the implementation of edupreneurship and business center in the school. The research was conducted by observation and interviews with informants who were directly involved in edupreneurship activities. The results of this study show that: 1) the implementation of education is carried out through the business center, 2) Learning in the business center is carried out through business practices involving Accounting students in market observation activities, inventory of consumer needs, ordering/purchasing from the business center, determining selling prices, recording transactions and making reports, as well as managing their own finances. This activity succeeded in fostering an entrepreneurial spirit which included confidence, the courage to take risks, focus on tasks and results, as well as honesty and thoroughness.